Native Aquatic and Wetland Plants: Arrow Arum, Peltandra virginica - Kimberly A. Moore; Luci E. Fisher; Carl J. Della Torre; Lyn A. Gettys (EDIS)
Arrow arum is a native aquatic and wetland plant that is a welcome addition to water gardens, aquatic ponds, and wetland restoration and mitigation sites. The species is broadly adapted and extremely common throughout Florida, and its perennial nature assures a stellar performance year after year. This new 3-page fact sheet provides an overview of this plant and discusses its distribution, habitat, propagation, and other uses. Written by Kimberly A. Moore, Luci E. Fisher, Carl J. Della Torre III, and Lyn A. Gettys, and published by the UF Department of Agronomy, October 2015.